2019
DOI: 10.1101/822791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic identification of the functional surface for RNA binding by Escherichia coli ProQ

Abstract: The FinO-domain-protein ProQ is an RNA-binding protein that has been known to play a role in osmoregulation in proteobacteria. Recently, ProQ has been shown to act as a global RNA-binding protein in Salmonella and E. coli, binding to dozens of small RNAs (sRNAs) and messenger RNAs (mRNAs) to regulate mRNA-expression levels through interactions with both 5' and 3' untranslated regions (UTRs). Despite excitement around ProQ as a novel global RNA-binding protein interacting with many sRNAs and mRNAs, and its pote… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 42 publications
5
33
0
Order By: Relevance
“…The HDX study suggested that the sRNA SraB contacts the linker and CTD of E. coli ProQ more extensively than the cspE 3ʹ-UTR (19). In agreement with this observation, the linker and the CTD regions of ProQ contributed to the binding of SibB sRNA, but not the cspE 3ʹ-UTR, when measured by the three-hybrid assay (30).…”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…The HDX study suggested that the sRNA SraB contacts the linker and CTD of E. coli ProQ more extensively than the cspE 3ʹ-UTR (19). In agreement with this observation, the linker and the CTD regions of ProQ contributed to the binding of SibB sRNA, but not the cspE 3ʹ-UTR, when measured by the three-hybrid assay (30).…”
Section: Introductionsupporting
confidence: 55%
“…Given that previous studies showed contributions of ProQ's FinO domain to RNA binding (19,29,30), the binding of this isolated domain to the six RNAs was also examined ( Fig. 3, Table 1, Suppl.…”
Section: The Isolated Fino Domain Of Proq Preferentially Binds Rnas Tmentioning
confidence: 99%
See 3 more Smart Citations